E-Services and Positioning of Passenger Ports in the Context of Cruise Tourism Promotion - Vitić-Ćetković, Andriela; Bauk, Sanja (Promet - Traffic&Transportation, 2014)
The paper positions the passenger sea ports in the context of cruise tourism on the basis of e-services they offer. The e-services of eleven passenger ports are categorized and then quantitatively evaluated by binary and ranking approaches. In general, the port e-services might be categorized according to their functionality as navigational, ship and passenger-related ones, logistics, business, marketing, entertainment, security, safety, environmental, etc. These services can be bidirectional informational and/or transactional. In this paper, only those port e-services related directly to the passengers’ needs, within the frame of cruise tourism, are taken into consideration and categorized as core, or as value-added ones, and as informational and/or transactional ones. Then, each of them is assigned an appropriate binary value (0/1), depending on whether the considered passenger port offers the related e-service or not. These values are employed in the evaluation of the analyzed passenger port e-services offered, and as a base for their positioning. The appropriate weights coefficients, obtained by ranking (Saaty method), were used in the process of the considered port final positioning on the cruise tourism e-market. Some additional analyses and recommendations in the direction of further positioning and promotion of the port of Kotor (Montenegro), as rising cruise tourism port (destination), are given as well.